Severe depression episode with an incredible improvement after electroconvulsive therapy - Rezmer, Jakub; Homa, Wojciech; Bogusz, Paweł; Soroka, Ewelina (Journal of Education, Health and Sport, 2024)
Aim: The primary aim of this article is to present a case study of a patient with severe depressive episode that was refractory to extensive pharmacological treatment, but exhibited remarkable improvement following electroconvulsive therapy (ECT). Materials and Methods: The patient’s medical records were obtained from II Department of Psychiatry and Psychiatric Rehabilitation, Medical University of Lublin. Cited literature was searched on the PubMed database using the following keywords: Major depressive disorder or MDD, Electroconvulsive therapy, and Benzodiazepine dependence. Results and conclusions: A 55-year-old woman with recurrent depressive disorder and benzodiazepine dependance, unresponsive to multiple medications, requested an ECT. She was then treated with a cycle of 12 Seizure Electroconvulsive Therapy (SECT) sessions. Initially bedridden with severe anxiety, suicidal thoughts, and no clinical improvement despite maximal pharmacotherapy, she exhibited significant improvement after three SECT sessions. Her anxiety decreased, suicidal ideation resolved, and symptoms of anergy and anhedonia diminished. At the end of the SECT cycle, the patient’s mood stabilised, and her activity level and social engagement increased. At discharge, she showed no suicidal ideation, tendencies, or psychotic symptoms. This case demonstrates the effectiveness of ECT in treating severe, pharmacologically resistant depressive episodes. It highlights the importance of considering patient requests in conjunction with clinical assessments to achieve positive outcomes. Raising awareness about ECT’s safety and efficacy among the public and mental health professionals is crucial for optimizing treatment strategies for severe depression. Proper qualification and timely administration of ECT can significantly enhance treatment outcomes beyond pharmacotherapy alone.